EKO-ARSITEKTUR PADA PERMUKIMAN TRADISIONAL DI DESA ADAT BUGBUG, KARANGASEM - Desak Made Sukma Widiani (Universitas Dwijendra, 2013)
Ecology in terms of architecture is the architecture process that must consider the relations among living things and between living things and the environment, energy and its interaction with the environment. The basic principle in the process of ecological architectural design is to combine nature with technology, using nature as a basis of design, conservation strategies, environmental improvement, and can be applied at all levels and scales to produce a form of buildings, landscapes, settlements and cities.Application of ecological architecture actually been seen since the first on traditional buildings made by our ancestors. Ecological architecture in buildings, especially traditional Balinese traditional houses can be seen from the building materials used are woods, bamboos, reeds, stones, as well as the functional form of the building and its relationship with nature and the environment. Ecological architecture also related to sustainable architecture, which is expected to eventually produce design concepts that are environmentally friendly architecture, come sustain ecosystems, using energy efficient, use natural resources efficiently without neglecting the welfare and comfort of human physical, social and economic unsustainable.This research was conducted aiming to find out how traditional settlement patterns at Bugbug village and understand how the relationship between ecological architecture with traditional settlements at Bugbug village from the environmental aspects, activities and of course architecture. While the results from the this study later is a visual form of the traditional settlement patterns at Bugbug village are still very traditional with a linear pattern, as well as the application of micro-eco-architecture, as seen from the elements of the dwelling, and the macro in the form of the relationship between citizens of the Village, occupancy, as well as the environment around the village in a descriptive analysis.Key words: ecological, traditional, environmentally friendly, efficient.